Examining the Effectiveness of Positive Thinking Focused on Improving Marital Relationships on Irrational Beliefs and Dyadic Coping in Women with Marital Conflict with Their Spouses - Aliasghari, Ali; Khademi, Ali; Rezaei Ghazalhajin, Elham (Psychology of Woman Journal, 2023)
Objective: This study aimed to examine the effectiveness of positive thinking focused on improving marital relationships on irrational beliefs and dyadic coping in women experiencing marital conflict with their spouses.Materials and Methods: The present study is a quasi-experimental design with pre-test, post-test, and control groups. The statistical population comprised women experiencing marital conflict with their spouses in Ardabil in 2022. The sample size was 30 participants, divided into experimental (15 participants) and control (15 participants) groups. The pre-test was administered, followed by the implementation of positive thinking training focused on improving marital relationships for the experimental group. Subsequently, post-tests were conducted for both groups. Data were collected using the Sanaei Marital Conflict Questionnaire, the Irrational Beliefs Questionnaire, and the Dyadic Coping Questionnaire. Data were analyzed using SPSS software (version 26) and multivariate covariance analysis.Findings: The results indicated significant differences in irrational beliefs and dyadic coping in women experiencing marital conflict with their spouses between the experimental group and the control group in the post-test phase (P < 0.01).Conclusion: Therefore, positive thinking interventions focused on improving marital relationships can be utilized to reduce irrational beliefs and enhance dyadic coping in women experiencing marital conflict with their spouses.